Flurbiprofen-Loaded Solid SNEDDS Preconcentrate for the Enhanced Solubility, In-Vitro Dissolution and Bioavailability in Rats - Rae Man Kim; Dong-Jin Jang; Yu Chul Kim; Jin-Ha Yoon; Kyoung Ah Min; Han-Joo Maeng; Kwan Hyung Cho (MDPI AG, 2018)
The aim of this work was to prepare and optimize a solid self-nanoemulsifying drug delivery system pre-concentrate (SSP) containing water-insoluble flurbiprofen (FL) using a novel pseudo-ternary phase diagram. The pseudo-ternary phase diagram, composed of FL as the drug and dispersion core, Kollisolv MCT 70 as the oil phase, and TPGS (tocopherol polyethylene glycol 1000 succinate) as the surfactant, was constructed for the determination of the SSP region. SSP was investigated in terms of particle size, physical state by differential scanning calorimetry (DSC) and powder X-ray diffraction (PXRD), in vitro dissolution and oral pharmacokinetics in rats. The determined SSP (FL/Kollisolv MCT 70/TPGS = 10/10/80, weight %) in the pseudo-ternary phase diagram had the melting point of 32.37 °C and uniform mean particle size of below 30 nm without any precipitation of FL in the dispersion. In the dissolution test, the SSP exhibited 95.70 ± 3.40% of release at 15 min, whereas the raw FL showed poor dissolution (i.e., 6.75 ± 1.30%) at that time point. In addition, the SSP showed the enhanced oral absorption (i.e., 1.93-fold increase in AUCinfinite) as compared to the suspension group of raw FL. Therefore, the developed SSP would be a promising drug delivery system with excellent solubilization, dissolution, and bioavailability for FL.